Identifying sources and sinks of scalars in a corn canopy with inverse Lagrangian dispersion analysis: II. Ammonia - Harper, L.A; Denmead, O.T; Sharpe, R.R (Agricultural and forest meteorology, 2000)
An inverse Lagrangian dispersion analysis was used to infer sources and sinks of ammonia (NH 3) in the canopy of a dense corn crop (LAI∼5) subject to frequent sprinkler irrigation with dairy effluent. Source strengths were calculated for four canopy layers using statistics of the canopy turbulence and measurements of atmospheric NH 3 concentrations at six heights within the canopy and two above it. The analysis was performed for 4 days of measurement, two immediately following and two several days after effluent application. The analysis provided estimates of the net loss of NH 3 from the canopy, which agreed well (within 20%) with conventional aerodynamic estimates of the flux of NH 3 in the crop boundary layer. In addition, it permitted an examination of processes of loss within the canopy. Small, but not insignificant NH 3 losses were inferred for the soil. These ranged from 4% of the total loss several days after effluent application to 30% on the day of application. Unexpectedly large losses occurred from the foliage in the top half of the canopy. Calculations of apparent ammonia compensation points for the corn leaves indicated that even days after the surface water had evaporated, compensation points were too high for the loss to be explained by diffusion through stomata. It was surmised that the loss was from residues remaining on foliage surfaces. Volatilization losses from the developed crop were estimated to be about 30% of the N applied, 18% coming from soil and foliage and 12% from spray losses during effluent application.